2011
DOI: 10.1093/europace/eur329
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of cardiac pacing in octogenarians and nonagenarians

Abstract: This large study of long-term cardiac pacing for bradycardia in octogenarians and nonagenarians showed a cumulative 5-year survival of ~50%, which compares with that of age- and sex-matched controls. These data suggest a beneficial impact of bradycardia pacing, restoring life expectancy to previous levels. The occurrence of PM complications during long-term follow-up is not infrequent with 18.1% of patients experiencing a PM-related complication during a mean of 5.8 years follow-up. The complication rate was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 28 publications
11
28
1
Order By: Relevance
“…The distribution of parameters in the study group (sex, age, and additional health conditions analysed) was comparable to that in previously examined populations of >80-year-olds [5,6,14,15,[18][19][20] . In contrast to the pre- viously quoted research studies, in this paper pharmacotherapy and selected laboratory parameters were analysed as well.…”
Section: Discussionsupporting
confidence: 80%
“…The distribution of parameters in the study group (sex, age, and additional health conditions analysed) was comparable to that in previously examined populations of >80-year-olds [5,6,14,15,[18][19][20] . In contrast to the pre- viously quoted research studies, in this paper pharmacotherapy and selected laboratory parameters were analysed as well.…”
Section: Discussionsupporting
confidence: 80%
“…Among the study population, 37 patients (59.7%) died, mainly from unknown or cardiovascular causes, and survival rates were 84.2% at 1 year, 66.9% at 2 years and 22.7% at 5 years; the median survival time was 30.2 months. These mortality rates are similar to those described previously by Udo et al in a population of octogenarians and nonagenarians implanted for the first time (86%, 75% and 49% after 1, 2 and 5 years [5]), and in nonagenarian non-recipients of pacemakers [26].…”
Section: Long-term Survivalsupporting
confidence: 90%
“…Women, underweight patients, low-volume centres and operators, dual-chamber devices, upgrading or lead revision and emergency out-of-hours procedures have been associated with a higher risk of complications [10]. In patients aged > 80 years, Udo et al reported significant complication rates, mostly lead-related, of 9.8% within 2 months and 6.9% during long-term follow-up; these rates were not different to those in patients aged < 80 years [5]. Similarly, very elderly patients did not seem to have more complications than younger patients in other studies [11,12].…”
Section: Procedural Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…However, survival for recipients without CVD matched that of the general population. This was also the case for the oldest old (octogenarians and nonagenarians) [3,4]. Similar findings for elderly patients without symptomatic heart disease were reported in earlier decades from a small study from Olmsted County, Minnesota [5], and survival for agesex-and comorbidity-matched Taiwanese nonagenarians implanted with PPMs from 2001-2012 was no worse than for controls [6].…”
Section: Introductionsupporting
confidence: 85%